JWST/NIRCam Probes Young Star Clusters in the Reionization Era Sunrise Arc - Vanzella, Eros; Claeyssens, Adélaïde; Welch, Brian; Adamo, Angela; Coe, Dan; Diego, Jose M.; Mahler, Guillaume; Khullar, Gourav; Kokorev, Vasily; Oguri, Masamune; Ravindranath, Swara; Furtak, Lukas J.; et al. (The Astrophysical journal, 2023)
Star cluster formation in the early universe and its contribution to reionization remains largely unconstrained to date. Here we present JWST/NIRCam imaging of the most highly magnified galaxy known at z ∼ 6, the Sunrise arc. We identify six young massive star clusters (YMCs) with measured radii spanning from ∼20 down to ∼1 pc (corrected for lensing magnification), estimated stellar masses of ∼10 6–7 M ⊙ , and ages of 1–30 Myr based on SED fitting to photometry measured in eight filters extending to rest frame 7000 Å. The resulting stellar mass surface densities are higher than 1000 M ⊙ pc −2 (up to a few 10 5 M ⊙ pc −2 ), and their inferred dynamical ages qualify the majority of these systems as gravitationally bound stellar clusters. The star cluster ages map the progression of star formation along the arc, with two evolved systems (≳10 Myr old) followed by very young clusters. The youngest stellar clusters (<5 Myr) show evidence of prominent H β +[O iii ] emission based on photometry with equivalent widths larger than >1000 Å rest frame and are hosted in a 200 pc sized star-forming complex. Such a region dominates the ionizing photon production with a high efficiency log ( ξ ion [ Hz erg − 1 ] ) ∼ 25.7 . A significant fraction of the recently formed stellar mass of the galaxy (10%–30%) occurred in these YMCs. We speculate that such sources of ionizing radiation boost the ionizing photon production efficiency, which eventually carves ionized channels that might favor the escape of Lyman continuum radiation. The survival of some of the clusters would make them the progenitors of massive and relatively metal-poor globular clusters in the local universe.